Perancangan Sistem Monitoring Penggunaan Daya Listrik/ Kwh Rumah Tangga Berbasis Iot Dan Android - Fergina, Anggun; Somantri, S; R, Rini Melani (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Electricity is a very important component of human life, especially in daily life. Electricity consists of several categories, one of which is the household category which we often encounter in the surrounding environment because it is used at home. Electronic devices are a necessity, when using electronic devices of course you need help with an electricity supply, and every house needs a device in the form of a KWH Meter (Kilowatt/Hour), but when using a KWH Meter (Kilowatt/Hour) currently users can only see electricity usage information. manually by looking directly at the token balance on the KWH Meter, this of course makes it difficult for users to know the contents of the token balance when they are outside the house, therefore a KWH (Kilowatt/Hour) usage monitoring tool is needed to find out how much it costs to use electricity. via Android. The result of this research is a system for monitoring the use of KWH (Kilowatt/Hours) Meters in the form of IoT (Internet of Things) devices and Android applications to help users find out information on power usage, voltage, current and electricity bills in real time.